2000
DOI: 10.1890/0012-9658(2000)081[1685:mdsiah]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Diffusive Spread in a Heterogeneous Population: A Movement Study With Stream Fish

Abstract: Using a mark–recapture technique in a small temperate stream, we described the movement of four fish species over a five‐month period and developed a mathematical model that described the observed movement patterns. The movement distributions were generally leptokurtic, and two of the four species demonstrated some degree of upstream bias. There was little difference in movement among species or through time. There were no temporal correlations in probability of movement, movement direction, or distance moved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
158
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(168 citation statements)
references
References 48 publications
9
158
1
Order By: Relevance
“…As in Petty and Grossman (2004), leptokurtosis was a general feature of the sculpin movement distributions in our study. Leptokurtosis can be an indication of significant intrapopulation variability in movement rates (Skalski and Gilliam 2000;Petty and Grossman 2004). We do not know if the Potomac sculpin population in Smith Creek comprises both mobile and sedentary subpopulations or whether individuals switch between mobile and sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…As in Petty and Grossman (2004), leptokurtosis was a general feature of the sculpin movement distributions in our study. Leptokurtosis can be an indication of significant intrapopulation variability in movement rates (Skalski and Gilliam 2000;Petty and Grossman 2004). We do not know if the Potomac sculpin population in Smith Creek comprises both mobile and sedentary subpopulations or whether individuals switch between mobile and sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…1). branches. Within-network dispersal has been described for a number of stream-associated organisms [e.g., invertebrates (31), fish (32,33), and salamanders (34,35)]. In contrast, overland dispersal is poorly characterized for most species, although studies have documented this dispersal pathway in stream invertebrates (22,36), observed short-distance overland movements in stream salamanders (35), and inferred overland dispersal in studies of genetic relatedness in stream salamanders (17) and invertebrates (37).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Pezold et al (1997) and Butler and Fairchild (2005) concluded that creek chub were year-round residents of small temperate streams, and Skalski and Gilliam (2000) found that creek chub do not display directional bias of movement during spring and summer months. The results of these studies coincide with our findings: marked creek chub were repeatedly captured at their station of original marking during the spring, summer, and autumn sampling periods; for creek chub displaying movement between sites, the numbers of upstream (three fish) and downstream (four fish) movements were comparable.…”
Section: Discussionmentioning
confidence: 99%